Environmental Degradation In Raja Ampat And The Reforestation Initiative Of Jerhemy Owen: A Qur'anic Perspective On The Dialectic Of Corruption And Restoration In QS. Al-A'Raf: 56 - Wildana Anjuma, Kunti; Mukaromah, Kholila (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2025)
Raja Ampat is recognized as one of the world’s most biodiverse marine and tropical forest conservation areas. However, in recent years, this region has faced severe ecological pressures due to massive natural resource exploitation, particularly through nickel mining activities conducted by PT Gag Nikel. Ironically, amid environmental degradation driven by short-term economic interests, there are still individuals who consciously choose to contribute to ecological restoration efforts, such as reforestation initiatives across various regions of Indonesia. One notable figure is Jerhemy Owen, a content creator and environmental activist, who launched a mission entitled Wenanam—meaning “we plant”—with the goal of planting 10,000 trees throughout Indonesia. Although his actions did not take place directly in Raja Ampat, his movement serves as a moral symbol that hope for ecological recovery remains alive. This phenomenon illustrates the dialectic between fasād (corruption) and iṣlāḥ (restoration) as articulated in the Qur’an, particularly in Surah Al-A‘rāf verse 56, which warns against spreading corruption on earth after God has set it right, and calls for living with a spiritual consciousness grounded in fear (khauf) and hope (ṭamaʿ) in His mercy. This article employs a qualitative method using a thematic tafsir (tafsīr mawḍū‘ī) approach and contextual analysis, referencing classical exegetical sources such as Tafsīr al-Ṭabarī and al-Qurṭubī, as well as contemporary commentaries like Tafsīr al-Misbah and Tafsīr Maudhū‘ī. The study focuses on the ecological paradox in which nature, which ought to be preserved, is instead exploited, while certain individuals strive to repair it with sincerity and moral commitment. As some destroy forests, others are willing to plant thousands of trees as a form of moral responsibility. The findings show that environmental exploitation in Raja Ampat constitutes a violation of the Islamic ecological principle of balance (mīzān), while Jerhemy Owen’s reforestation efforts exemplify the actualization of iṣlāḥ. Therefore, integrating Qur’anic interpretation with environmental activism is essential to constructing an ethical framework for ecological responsibility that is relevant, solution-oriented, and responsive to both local and global environmental crises.